Design of a multi-band antenna - Tang, Jun (2019)
The aim of this final year project is to design one printed bow-tie dipole multiband antenna operating frequency range between 900MHz~2.7GHz under three conditions (air, above a conducting ground at height h, in a cavity-backed). The process of solving the challenge which we faced in antenna design is also a learning process. The antenna design need consider a lot of parameters like: substrate materials type used, feeding scheme and dimensions of the antenna, reflection coefficient and antenna gain, radiation patterns. The designed antenna is constructed and simulated by ANSYS High-Frequency Structural Simulator (HFSS) and simulation results under three different conditions also need to be discussed and analyzed. The most important aim of this final year project is to get better antenna performance by varying the antenna structural dimension or adjust the height between antennas to conducting ground.